Reactions with hydrazonoyl halides 66: Synthesis of some new 1,3,4-thiadiazoles, triazolino[4,3-a]pyrimidines and isoxazolo[3,4-d]pyridazines containing coumarin moiety - Abdelhamid, Abdou Osman; Fahmi, Abdelgawad Ali; Ali, Abeer Bahlol (European Journal of Chemistry, 2011)
2,3-Dihydro-1,3,4-thiadiazoles, triazolino[4,3-a]pyrimidines, isoxazoles and isoxazolo[3,4-d]pyridazines containing coumarin moities were synthesized from the reactions of methyl (or benzyl) carbodithioate, pyrimidine-2-thione and 3-(3-(dimethylamino)acryloyl)-2H-chromen-2-one derivatives with C-coumarinoyl-N-phenylhydrazonoyl bromide. The structures of all the newly synthesized compounds were confirmed by elemental analyses and spectral data.